Selection Pressures* on Special Education Teacher Preparation: Issues Shaping Our Future. (February 2014) - Dukes, Charles; Darling, Sharon M.; Doan, Kim
In this introduction to the special issue on evolving changes in our field, we have intentionally chosen to use the power of a vastly different metaphor to promote deep reflection. Specifically, we will introduce the notion of selection pressures and its impact on an evolutionary process, illustrating how special education teacher education has changed or evolved. We discuss these changes in the context of the 21st century and contextualize this explanation by representing special education teacher education as an avatar, thereby borrowing from the virtual world. We borrow concepts from natural science and the virtual world to help promote a new understanding of the nature of special education teacher education. Several selection pressures have been identified as affecting and moving forward special education teacher education such as (a) professional development/course delivery, (b) field experiences/mentoring induction, and (c) performance assessment. Each factor is considered with regard to its influence on the evolving nature of the 21st-century special education teacher education.